The Status of Occupational Noise in Some Selected Factories on Libya (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper occupational noise levels atselected factories were measured and compared with the international permissible levels using the integratingsound level meter (Quest 2800) during the year 2007.The calibration of the instrument was carried out beforeand after each measurement using the acousticcalibrator (Quest CA-12B calibrator). The methodwhich was followed was measuring the sound pressurelevel of the different noise sources over a broadfrequency band covering the audible frequency rangeusing the (Octave band filter, model OB-100),disregarding variation with time.From the obtained results, some noise levels whichwere recorded were within the permissible levels i.e.below 90 dBA and some noise levels were higher thanthe permissible limit as at Janzoor textile factory(95dBA), Benghazi Macaroni factory (100dBA), andnear the air blowers at Zletin cement factory, Benghazicement factory (97-100 dBA) in these cases suggestionswere made to minimize the problem.